Using Principal Component Analysis to Identify Components Predictive of Shape Index in Chicken, Quail and Guinea Fowl - Shaker , Ahmed S.; Amin, Questan A.; Akram, Shilan A.; Kirkuki, Shahla M.S.; Talabani, Rozhgar S. Bayez; Mustafa, Nidhal A.; Mohammed, Mohammed Sardar (International Journal of Poultry Science, 2019)
Background and Objective: The shape index of avian eggs is used as an indicator for predicting chick weight, hatchability and eggshell quality. However, the components that most contribute to shape index remain unknown. The aim of this study was to provide an objective description of shape index using principal component analysis and to predict shape index from egg measurements derived from this analysis. Materials and Methods: The present study was carried out in the Animal Production Department laboratories of Sulaimani University, Sulaimani, Iraq. From July 2017 to February 2018, a total of 98, 95 and 56 chicken, quail and guinea fowl eggs respectively were collected from local markets. Digital balance and vernier calipers were used to measure the traits. Then descriptive analysis, correlations and principal component analysis were determined by using SPSS program. Results: The guinea fowl and quail had high egg shape indexes of 79.24 and 79.00% respectively, followed by the chicken (75.19%). The relationships between the shape index and the majority of the egg components were positive and significant (p